Edukasi Maternal Perspektif Al-Qur’an - Ahmad Zain Sarnoto; Riadi Jannah Siregar (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2019)
Maternal education in the Qur'an can be understood in the sense of: Education about being a mother relating to the role of the mother during pregnancy and postnatal child care, including maternal education which includes the role of the mother in the public and domestic environments The process of education stages of maternal education which consists of three stages, namely: 1. Pre-marital period, is education for women (also for men) to understand about how to find a partner in accordance with his teachings. about the Qur'an and hadith, mental readiness in facing marriage and getting offspring; 2. Prenatal period, namely mental readiness education, awareness of maintaining physical health, including maternal efforts to build emotional closeness and spiritual education to prospective babies while still in the womb. It aims to develop and develop innate potential in the form of spiritual, emotional, intellectual and social intelligence; and 3. Post-delivery, namely education that includes breastfeeding education to understand the importance of exclusive breastfeeding for children's health, shape the character of children, help children in building social relations and independence, and oversee the process of children's education both formally, informally and informally